Different Responses of Muscle Sympathetic Nerve Activity to Dapagliflozin Between Patients With Type 2 Diabetes With and Without Heart Failure - Takuto Hamaoka; Hisayoshi Murai; Tadayuki Hirai; Hiroyuki Sugimoto; Yusuke Mukai; Oto Inoue; Shinichiro Takashima; Takeshi Kato; Shigeo Takata; Soichiro Usui; Kenji Sakata; Masa‐Aki Kawashiri; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Sodium‐glucose cotransporter 2 inhibitors improve cardiovascular outcomes in patients with diabetes with and without heart failure (HF). However, their influence on sympathetic nerve activity (SNA) remains unclear. The purpose of this study was to evaluate the effect of sodium‐glucose cotransporter 2 inhibitors on SNA and compare the responses of SNA to sodium‐glucose cotransporter 2 inhibitors in patients with type 2 diabetes with and without HF. Methods and Results Eighteen patients with type 2 diabetes, 10 with HF (65.4±3.68 years) and 8 without HF (63.3±3.62 years), were included. Muscle SNA (MSNA), heart rate, and blood pressure were recorded before and 12 weeks after administration of dapagliflozin (5 mg/day). Sympathetic and cardiovagal baroreflex sensitivity were simultaneously calculated. Brain natriuretic peptide level increased significantly at baseline in patients with HF than those without HF, while MSNA, blood pressure, and hemoglobin A1c did not differ between the 2 groups. Fasting blood glucose and homeostatic model assessment of insulin resistance did not change in either group after administering dapagliflozin. MSNA decreased significantly in both groups. However, the reduction in MSNA was significantly higher in patients with HF than patients with non‐HF (−20.2±3.46 versus −9.38±3.65 bursts/100 heartbeats; P=0.049), which was concordant with the decrease in brain natriuretic peptide. Conclusions Dapagliflozin significantly decreased MSNA in patients with type 2 diabetes regardless of its blood glucose‐lowering effect. Moreover, the reduction in MSNA was more prominent in patients with HF than in patients with non‐HF. These results indicate that the cardioprotective effects of sodium‐glucose cotransporter 2 inhibitors may, in part, be attributed to improved SNA.